Antidepressant, analgesic activity and SAR studies of substituted benzimidazoles - Siddiqui, Nadeem; Alam, Md Shamsher; Sahu, Meeta; Yar, M. Shahar; Alam, Ozair; Siddiqui, Mohammad Jamshed (Asian Pharma Press, 2016)
Purpose. Benzimidazole class of compound is found to have diverse biological properties. From the literature study, it is observed that depression is a severe mental disease affecting a huge population and pain is affecting about 20% of world population. In continuation of our previous research work, we selected benzimidazole pharmacophore to further explore its pharmacological activities. Methods. Forced swim test and Thermal stimulus test were used to assess the antidepressant and analgesic activity of synthesized benzimidazole analogs. Results. The antidepressant activity results showed that compound 3j was found most potent having Mean ± SEM value 21.6 ± 0.8 for treated group. Furthermore, in the analgesic test, 3b, 3j, and 3o showed Mean ± SEM values; 1.8 ± 0.10, 2.3 ± 0.10 and 2.2 ± 0.10, respectively. The study results suggested that these compounds could be explored further for the development of better antidepressant and analgesic agents. Conclusion. From the present study, it may be concluded that these active benzimidazole derivatives have been found to possess potential antidepressant and analgesic activity